The Effect of Rheumatic Exercise Reducing the Scale Rheumatoid Arthritis Joint Pain Elderly at UPTD Social Services for Elderly in Binjai - Rotua Elvina Pakpahan; Helinida Saragih; Rehulina Silalahi (Pusat Riset dan Inovasi Nasional, 2025)
Rheumatoid arthritis joint pain in the elderly is a result of the body's calcification and reduction in synovium fluid lining the joints, or a disease caused by degenerative changes in the musculoskeletal system. Most elderly people still use inappropriate methods such as pharmacological therapy (drugs) to treat joint pain. The non-pharmacological method is by using rheumatic exercises. The aim of this research is to determine the effect of rheumatic exercise on reducing the scale of rheumatoid arthritis joint pain in the elderly at UPTD social services for the elderly in Binjai. This research is a quantitative study using pre-experimental design method using one group pre and post test design approach, technique. Sampling was purposive sampling with 19 respondents using G-power software. The instruments used in this research are the Numeric Rating Scale observation sheet and rheumatic gymnastics SOP, which is tested using the paired T-Test. The results of statistical tests show that there is an effect of rheumatic exercise on reducing the scale of rheumatoid arthritis joint pain in the elderly at Binjai Elderly Social Services UPTD 2024. With the results of the paired t-test, it is obtained that ρ value = 0.001. Rheumatic exercise as an alternative treatment that can reduce the scale of rheumatoid arthritis joint pain in the elderly.